Railway infrastructure of Ukraine as a factor of soil chemical hazard (analytical overview) - Danchenko, Yuliya; Bosak, Pavlo; Shukel, Igor; Popovych, Vasyl (International Conference “Environmental Engineering”, 2023)
To reach the aim in solving these tasks, the following theoretical methods of research were used, mainly analysis, experimental data, complex assessment of hazardous influence of railway infrastructure on the environment, mainly soil chemical pollution, which are an essential part of railway infrastructure. Considering the comparative characteristics, we can make a prognosis on any heavy metal impact with excessive content of acid and alkaline properties of polluted soils. A result of scientific research an analytical review of the issue of railway infrastructure in Ukraine as a factor of soil chemical hazard and determination of the main sources of pollution among the enterprises of rail transport.